Grain Yield, Yield Components and Relative Water Content in Maize (Zea mays L.) under Water Deficit Stress and two Mycorrhizal Fungi - v Nasrollahzade; m Yusefi; a Ghosemi; a Bandehhagh (Journal of Agricultural Science and Sustainable Production, 2017)
The effects of two mycorrhizal fungi species on grain yield, yield components, relative water content (RWC) and chlorophyll content in maize (SC704) under water deficit stress, under field experiment was assessed out as a split plot design with four replications in 2016 at Moghan Research Station. Water stress treatments included commonly available irrigation water referred to as control and the interrupted irrigation before flowering as the main plot, and two different mycorrhiza species, including Glomus mosseae and Glomus etunicatum and also a control (without any inoculation) as sub plots. Results showed that water stress significantly decreased grain yield, yield components, relative water content (RWC) and chlorophyll content. The applied water deficit stress reduced grain yield, yield components, RWC and chlorophyll content about 14, 13, 20 and 13 percent, respectively. Mycorrhizal fungi increased plant height, RWC and chlorophyll content in maize. Interaction between water stress and strains of mycorrhiza had only an impact on grain yield and 100-seed weight. The maximum grain yield and 100-seed weight were recorded in plots irrigated in normal condition and inoculated with G. mosseae species on control irrigation. Based on the results of this study, for enhancing grain yield and chlorophyll content using mycorrhizal fungi especially, G. mosseae species was recommended.